2013, Nr. 14, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting and auditing challengesInese Vigante, Ruta Sneidere, Social accounting and its contribution to society, 7Rasa Kanapickienė, Internal control instruments in the accounting policy of public sector entities, 17Darius Vaicekauskas, Types of audit quality research: their advantages and disadvantages, 30Evelina Stankevič, Performance audit analysis done by the national audit office of Lithuania, 41Gintarė Giriūnienė, Raminta Benetytė, Evaluation of tax audit strategies, 52Analysis and forecasting of enterprise‘ activityLukas Giriūnas, Jonas Mackevičius, Romualdas Valkauskas, Clusterization of reasons for bankruptcy of enterprises, 60Lukas Giriūnas, Aivaras Kazlauskas, Research of companies bankruptcy and its procedure, 72Judita Urbonaitė, Milda Kvekšienė, Mathematical methods for forecasting the company's financial results, 83Research of tax systemsMonika Melnykaitė, Agnė Ramanauskaitė, Assessment of bringing in the progressive income taxation in Lithuania, 96Lina Šalnytė, Giedrė Balkytė, Comparative analysis of Lithuanian and Polish taxation system, 110Analysis of study processBirutė Jukonienė, Ona Gudaitienė, Melanija Sinevičienė, The final thesis – learning outcome of professional bachelor., 121
Keywords: none